Characteristics of School Administrators in the 21st Century Affecting Success in School Academic Administration Under the Secondary Educational Service Area Office Bangkok 1 - Kruakoh, Wilawan; Boonphadung, Suttipong (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Academic administration was the heart of educational institution administration, which is to provide quality education. which depends on academic work, to encourage learners to achieve the stated educational goals with the utmost efficiency. The characteristics of executives are indicators that affect good or bad actions. Therefore, executives must have good characteristics have knowledge and ability Be a good social person have internal motivation Have an attitude, and have good human relations, etc. The objectives of this research are 1. to study the characteristics of educational institution administrators in the 21st century 2) to study the level of success in school academic administration 3) to relate the characteristics of educational institution administrators in the 21st century that affect the success of the school's academic administration. 4) To study the characteristics of educational institution administrators in the 21st century that affect the success of the school's academic administration under the jurisdiction of the Bangkok Secondary Educational Service Area Office, Area 1, Methodology: this study is a survey study. the sample group included school administrators and teachers in basic educational institutions. Under the jurisdiction of the Bangkok Secondary Educational Service Area Office, Area 1, a total of 355 students were sampled using stratified random sampling. according to the size of the educational institution. The research instrument was a questionnaire. The reliability value is 0.976. Statistics used in data analysis include percentage, mean, and standard deviation. Pearson correlation coefficient and stepwise multiple regression analysis. Results: (1) Overall characteristics of school administrators in the 21st century were at a high level. (2) Success in school academic administration overall at a high level. (3) Characteristics of school administrators in the 21st century that affect success in school academic administration. There is a high level of positive correlation. Statistically significant at the .01 level when considering the relationship between the characteristics of school administrators in the 21st century that affect the success of school academic administration. For each variable, it was found that there was a positive relationship with statistical significance at the .01 level. All variables had a low level of positive relationship for 1 variable, 1 variable was at a medium level, and was at a high level for 4 variables (r = 0.364-0.810) can jointly predict the success of the school's academic administration at 32.00 percent, written as a forecast equation as follows. The forecast equation in raw score form is as follows: Y´ = 3.707 + .235X4+ .165X1 + .105X5 The forecast equation Forecast in standard score form is as follows: Z´y = .531X4 + .274X1, + .235X5 Conclusion: The study's findings underscore the high overall characteristics of school administrators in the 21st century and the corresponding success in school academic administration. Notably, a statistically significant positive correlation was identified between these characteristics and the achievement of academic administration success. The results emphasize the importance of these 21st-century administrator traits in predicting and contributing to the overall success of school academic administration.